Urban stream rehabilitation in a densely populated Brazilian metropolis - Macedo, Diego R.; Callisto, Marcos; Linares, Marden S.; Hughes, Robert M.; Romano, Bruna M. L.; Rothe-Neves, Moana; Silveira, Juliana S. (Frontiers in Environmental Science, 2022)
Environmental rehabilitation of urban streams has been widely applied in Global North countries, at least since the 1970s, but it is a recent approach in Global South countries. The objective of this paper is to evaluate whether the rehabilitation experience carried out since 2007 in three urban stream sites in the third-largest Brazilian metropolis (c. 5.5 million inhabitants) was and continues to be effective in terms of socio-environmental improvement after 10 years of interventions. These interventions included the rehabilitation of watercourses (e.g., improvement of water quality through the management of sewage and garbage, stabilization of riverbanks, revegetation of riparian zones, riverbed naturalization, removal of riverbank housing). We evaluated water quality, physical habitat structure, and benthic macroinvertebrate assemblages in three test sites in three sampling periods: pre-intervention (2004-2007), early post-intervention (2008-2011) and late post-intervention (2018-2019). Additionally, three reference-stream sites (2018-2019) were assessed to compare the conditions of the three tested sites versus the reference sites. We also assessed social perceptions concerning the interventions through questionnaires given to 180 urban stream residents at the three tested sites in early and late post-rehabilitation (215 in 2008, 180 in 2019). The results of water quality monitoring showed a significant improvement in most parameters used to calculate the Water Quality Index (WQI) in the early intervention phase, and WQI scores have improved since. The physical habitat and macroinvertebrate indicators indicated moderate improvements. The residents’ social perceptions indicated increased appreciation of the environmental improvements over 10 y. Given the results in Belo Horizonte, we believe that implementation and evaluation of similar projects and programs aimed at rehabilitating urban streams are technically viable using our approaches throughout the Global South.